Increasing Community Awareness of Household Waste Management Through Environmental Education - Malik, Amalia; Hardiyani, Rini; Puspita, Helda Jaya; Dyah Larasati, Nova Hidayati; Tarigan, Rallyanta (Lembaga Dongan Dosen, 2025)
Household waste management in Patrang Village, Jember Regency, still faces the challenge of low community awareness in sorting waste at the source. This community service activity aims to enhance residents' knowledge and attitudes through an educational approach based on the Theory of Planned Behavior. The methods include pretest surveys, counseling, practical demonstrations, and posttests with 20 respondents. The pretest results showed that 90% of respondents had not yet sorted waste, although most were aware of the negative impact of improper waste disposal. After the education, there was a significant increase in understanding and pro-environmental attitudes, especially the readiness to sort waste at home. These findings indicate that educational and participatory approaches are effective in encouraging changes in waste management behavior. It is recommended that similar programs be conducted sustainably and involve more residents to support the creation of a clean and healthy environment.